The Jurisprudential - Legal Analysis of Speeding up in the Execution of a Civil Judgment with Emphasizing on the Provisional Execution - Amir Entezari; Rasoul Maghsoudpour; Sayyed Muhsen Husseini Pouya; Ahmad Taji (آموزه‌‌های فقه مدني, 2021)
Ahmad Taji (Assistant professor at Islamic Azad University of Neyshābūr) It should be stated that the enforcement of the order is the ultimate goal of the process of procedure but the governing rules state that the condition for enforcing judgment is the certainty of the decision or verdict and it has not been considered a system for the provisional execution in the statutory law or statute law except in specific cases. While this institute previously in the article 191 of the civil procedural law enacted 25/06/1318 and based on the origination of this law which is adopted from the law of France had been permitted by the legislature. In this paper with analytic-descriptive method, firstly speeding up in the execution of judgments has been pronounced then according to its importance, the provisional execution has been surveyed. It is going to prove that the provisional execution of judgment has been an appropriate strategy to vindicate (demonstrate) and speeding up in judicial proceedings has an Islamic jurisprudential record and there are hadiths in fiqh that indicate speeding up and not putting off in the stage of adjudication that it can be with the unity criterion a proof for the legality of the provisional execution in cases that the irrevocable damage is imagined while it is basically in fiqh, the adjudication is made within one step and the verdicts (decisions) are final (absolute) and with studying instances of the provisional execution in the present law, it is answered to this question that with induction in instances it is impossible to achieve to a common principle and an adopted (extracted) judgment. Therefore, the omission of the institution of the provisional execution of judgment from the code of civil procedure is an effective fault and there is necessary the legislature (law maker) to legislate it again.